College-Major Choice to College-Then-Major Choice - Bordon, Paola; Fu, Chao (Review of Economic Studies, 2015)
Many countries use college-major-specific admissions policies that require a student to choose a college-major pair jointly. Given the potential of student-major mismatches, we explore the equilibrium effects of postponing student choice of major. We develop a sorting equilibrium model under the college-major-specific admissions regime, allowing for match uncertainty and peer effects. We estimate the model using Chilean data. We introduce the counterfactual regime as a Stackelberg game in which a social planner chooses college-specific admissions policies and students make enrollment decisions, learn about their fits to various majors before choosing one. Our estimates indicate that switching from the baseline to the counterfactual regime leads to a 1% increase in average student welfare and that it is more likely to benefit female, low-income and/or low-ability students.